Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content 1. Research priorities in the administration of public education in The Kingdom of Saudi Arabia Dr. Manal Abdulaziz Alsalem,Mrs. Mashael Saleh Aljuwayid, Mrs. Mashael Mohammed Alghurayr 2. Determinants of selecting the national wrestling team juniors in training centers in the capital, Sana’a Mr. Kamal Muhammad Al-Taweel, Prof. Ibrahim Ali Al-Warafi 3. The impact of transformational leadership on the decision-making process in secondary schools in Tabuk Mr. Fahad A. Albalawi 4. The reality of application administrative governance at King Abdulaziz University from point of view of teaching faculty members Mrs. Mona Mohammed Alzahrani, Dr. Omar Mohammed Badawood 5. The effectiveness of a proposed training program based on an adaptive e-learning environment in developing productive thinking skills among productive families in Jeddah Mrs. Hanin Muhammad Zuhair Najjar, Prof. Suhail Salem Al-Harbi 6. Priorities of Appropriate Intervention to Empowering People with Developmental Disorders and Integrate them into Social Life from the Point of View of their Families Mrs. Amani O. Abuzahera 7. The Extent of Undergraduate Student Participation in Conducting Scientific Research at The University of Nizwa in the Sultanate of Oman Dr. Radhiya Sulaiman Al-Habsi , Mrs. Ikram Hamad Ali Al-Maadi , Mr. Ammar Saeed Amer Al-Salmani